Hearth and Home in Medieval Iceland: Understanding Chronic Respiratory Infection, Environment and the Vulnerable Child - Collins, Cecilia R. (Scandinavian-Canadian Studies / Études scandinaves au Canada)

(untitled) (Association for the Advancement of Scandinavian Studies in Canada, 2026)
The study of otitis media in palaeopathology holds tremendous implications for transforming understanding of the impact of partial or total hearing loss in past populations. The lived experience is scaffolded in the human and environmental entanglements which acknowledge the dwellings, landscapes and the embodiment of biological, social and cultural experiences. Analysis of the prevalence of otitis media and sinusitis at four medieval Icelandic sites: Hofstaðir, Keldudalur, Skeljastaðir and Skriðuklaustur revealed that a number of adults and children alike were affected by chronic respiratory infection, and specifically featuring endemic tuberculosis in this population, and consequently a number of individuals also likely suffered from pathological hearing loss. Finally, the methods allow new inferences in understanding the extent of hearing loss as a hidden disability in the past.